Learning Interest in Graphic Design Training Participants in the Prima Data Course and Training Institute in Padang City - Anggraini, Maimila; Wisroni, Wisroni (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research was motivated by the high participation of graphic design training participants carried out by the Padang Data Training and Prima Institute. This was allegedly due to the interest of the trainees themselves. This type of research is quantitative descriptive research. The population in this study were all graphic design training participants in the Padang Prima Data Course and Training Institute, totaling 30 people. Samples were taken 75%, namely 22 people using cluster random sampling techniques. Data collection techniques in this study used a questionnaire. The tool in data collection is a list of written statements. Data analysis techniques use percentage calculations. The results of the study found that (1) the trainners had a very high feeling of participating in the neural design training (2) the trainees had a very high interest in attending the neural design training, and (3) the trainees had a very high awareness in participating in the training neural design. It is recommended to (1) trainees, in order to maintain interest in learning in graphic design training at Padang Data Prima Training and Course Institute; (2) instructor, in order to create a conducive social atmosphere in the learning process in graphic design training at Padang Data Prima Training Course and Institute.